e-Learning development in medical physics and engineering - Tabakov, S (Department of Biomedical Imaging, Faculty of Medicine, University of Malaya, Malaysia, 2008)
Medical Physics and Engineering was among the first professions to develop and apply e-Learning (e-L). The profession provides excellent background for application of simulations and other e-L materials. The paper describes several layers for e-L development: Programming specific simulations; Building e-L modules; Development of e-L web-based programmes. The paper shows examples from these layers and outlines their specificities. At the end, the newest e-L development (project EMITEL) is briefly introduced and the necessity of a regularly updated list of e-L activities is emphasised.